Development of Self-Concept Rubik's Media in Orientation Services to Help Students Self-Identify - Achfa Yusra Panjaitan; Khairuddin Khairuddin (International Journal of Post Axial: Futuristic Teaching and Learning, 2026)
This study aims to develop a "self-concept Rubik's cube" medium that is valid and practical for use in orientation services to facilitate self-discovery among Grade X students at a private high school in Bandung. The researcher employed the Research and Development (R&D) method, utilizing the Four-D (4D) development model: Define, Design, Develop, and Disseminate. Media expert evaluations rated the self-concept Rubik's cube as highly valid, with a total average score of 88.16%. Subject matter expert evaluations also rated it as highly valid, with a total average score of 87.50%. Based on the assessment criteria, these results indicate that the medium and content of the self-concept Rubik's cube are highly valid and suitable for use in orientation services to assist students with self-discovery. Questionnaire results from teachers yielded a total average score of 92.50%, while results from students yielded an average score of 87.18%. Based on the assessment criteria derived from teacher and student responses, the self-concept Rubik's cube is considered highly practical for use in orientation services. In conclusion, the self-concept Rubik's cube medium for orientation services in Grade X at the private high school in Bandung is valid and practical for assisting students with self-discovery.